Near-death experiences - Landau, Elaine (Brookfield, Conn. : Millbrook Press, 1996)
Describes various categories of near-death experiences and provides information about how scientists study unknown phenomena.
Includes bibliographical references (p. 45) and index.
Keywords: Near-death experiences -- Juvenile literature; Near-death experiences